The Influence of User Satisfaction and Perceived Security on the Intention to Use QRIS Merchant among MSMEs in Kubu Raya Regency - Sukardi, Sukardi (Electronic Journal of Education, Social Economics and Technology, 2026)
This study aims to analyze the influence of user satisfaction and perceived security on the intention to use QRIS merchant among MSMEs in Kubu Raya Regency. The research employs a quantitative approach with an associative design. The population consists of all MSME actors using QRIS merchants in Kubu Raya Regency totaling 47,100 merchants. The sample size was determined using the Slovin formula with a 10% margin of error, resulting in 100 respondents selected through purposive sampling with the following criteria: active QRIS merchants, having used QRIS for at least three months, and directly involved in managing business transactions. Primary data were collected through questionnaires distributed to MSME actors using QRIS merchants, while secondary data were obtained from official publications related to the development of QRIS merchants. Data analysis was conducted using SPSS through instrument testing (validity and reliability), classical assumption tests (normality, linearity, and multicollinearity), and multiple linear regression. The results show the regression equation Y = 1.516 + 0.263X₁ + 0.248X₂, with a correlation coefficient R = 0.580 (moderate relationship) and a coefficient of determination R² = 0.337, meaning that 33.7% of the variation in intention to use is explained by user satisfaction and perceived security. The simultaneous test indicates that user satisfaction and perceived security jointly have a significant effect on intention to use. The partial test indicates that user satisfaction and perceived security have a positive and significant effect on intention to use. In conclusion, improving the quality of user experience and strengthening transaction security aspects are key factors in maintaining the sustainability of QRIS merchant usage among MSMEs in Kubu Raya Regency.